2001
DOI: 10.3354/meps221029
|View full text |Cite
|
Sign up to set email alerts
|

Protist control of phytoplankton growth in the subtropical north-east Atlantic

Abstract: The grazing impact of protists on phytoplankton primary production in a highly oligotrophic area of the subtropical north-east Atlantic, south-east of the Azores, was studied using the dilution method. The phytoplankton community in the experiments, analysed by flow-cytometry, was dominated by Prochlorococcus and Synechococcus although larger phototrophic groups, beyond flow-cytometry sensitivity, were also present. The microzooplankton community was dominated by small gymnodinoid dinoflagellates and aloricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 39 publications
9
55
0
1
Order By: Relevance
“…The high µ/µ n (approximate to or higher than one) indicated that phytoplankton growth was only slightly or even not nutrient-limited during the summer cruise (Table 1). Similar results in the oligotrophic subtropical Northeast Atlantic have also been reported (Cáceres et al, 2013;Quevedo and Anadón, 2001). In contrast, severe nutrient limitation indicated by the lower µ/µ n (0.54 ± 0.30) was observed during the winter, which may account for part of the low µ (Table 5).…”
Section: East Asian Monsoon Influencing Seasonal Variations In Phytopsupporting
confidence: 64%
See 1 more Smart Citation
“…The high µ/µ n (approximate to or higher than one) indicated that phytoplankton growth was only slightly or even not nutrient-limited during the summer cruise (Table 1). Similar results in the oligotrophic subtropical Northeast Atlantic have also been reported (Cáceres et al, 2013;Quevedo and Anadón, 2001). In contrast, severe nutrient limitation indicated by the lower µ/µ n (0.54 ± 0.30) was observed during the winter, which may account for part of the low µ (Table 5).…”
Section: East Asian Monsoon Influencing Seasonal Variations In Phytopsupporting
confidence: 64%
“…Non-linear responses were usually observed in eutrophic waters with high prey abundance (Elser and Frees, 1995;Gallegos, 1989;Teixeira and Figueiras, 2009). Nonlinear feeding responses in dilution experiments conducted in the oligotrophic subtropical Northeast Atlantic in summer have also been reported by Quevedo and Anadón (2001) and Cáceres et al (2013). However, the authors did not explain the underlying reasons for these phenomena.…”
Section: Non-linear Feeding Responsesmentioning
confidence: 47%
“…This broad term encompasses the heterotrophic nanoflagellates, ciliates, and dinoflagellates, all which have been reported to feed on Synechococcus [21,15,85,20,44] and may be important classes of grazers at MVCO. These organisms can quickly react to and take advantage of an increase in prey cells as their own cell division rates can match or exceed those of Synechococcus [52].…”
Section: Relationships Between Division Rate and Loss Ratementioning
confidence: 99%
“…Production can be expressed as the rate of synthesis of cells or cell mass: production=µ×biomass, where µ is the specific growth rate of the population expressed in units of inverse time t −1 (Ducklow, 2000). Phytoplankton µ estimates vary widely from values of around 0.1-0.3 d −1 (Letelier et al, 1996;Marañon et al, 2000Marañon et al, , 2005 to 1-2 d −1 (Laws et al, 1987;Quevedo and Anadon, 2001). Bacterial µ estimates also vary widely, from very low values 0.004-0.25 d −1 (Sherr et al, 2001;Van Wambeke, 2007b) to higher values of around 2-10 d −1 (Ducklow, 1983;Jones et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…heterotrophic bacterial µ. The two most common direct methods, applicable to both heterotrophic bacteria and phytoplankton, are (1) to observe the frequency of dividing cells (Hagstrom et al, 1979) and (2) the dilution technique (Landry and Hassett, 1982;Quevedo and Anadon, 2001). Direct methods are difficult to set up on board so microbial growth rates are commonly calculated from production and standing stock data (Ducklow, 2000).…”
Section: Introductionmentioning
confidence: 99%